1988
DOI: 10.1042/bj2540489
|View full text |Cite
|
Sign up to set email alerts
|

A water molecule participates in the secondary structure of hyaluronan

Abstract: The structure of hyaluronan was investigated in water/dimethyl sulphoxide mixtures by using high-field n.m.r. and space-filling molecular models. The secondary structure previously established in detail in 'dry' dimethyl sulphoxide [Heatley, Scott & Hull (1984) Biochem. J. 220, 197-205] undergoes changes on addition of water, compatible with the incorporation of a water bridge between the uronate carboxylate and acetamido NH groups. Molecular models show that such a configuration is highly probable, and satura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
95
1
3

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(105 citation statements)
references
References 15 publications
6
95
1
3
Order By: Relevance
“…In H20-containing solution, a water bridge substituted for the direct H bond N H + O -e . r 0 [12]. Computer simulation using molecular dynamics confirmed that the experimentally observed twofold helix was preferred and stable in water, but in vucuo, threefold and fourfold configurations were also adopted, within the same chain [13].…”
mentioning
confidence: 71%
“…In H20-containing solution, a water bridge substituted for the direct H bond N H + O -e . r 0 [12]. Computer simulation using molecular dynamics confirmed that the experimentally observed twofold helix was preferred and stable in water, but in vucuo, threefold and fourfold configurations were also adopted, within the same chain [13].…”
mentioning
confidence: 71%
“…The properties of these forms depend on the concentration and molecular weight of HA in the aqueous solution. Heatley et al (23) suggested that a high concentration of higher molecular weight HA (Ͼ1.0 mg/mL) produces random coils or chains that become entangled to form extended three-dimensional structures, and chain-chain overlap occurs. When the HA concentration is Ͻ0.1%, the HA molecules do not overlap (24).…”
Section: Discussionmentioning
confidence: 99%
“…NMR spectroscopy allowed the proposal of an hydrogen bond network to describe the conformation of HA in aqueous solution and its interactions with water molecules. [22][23][24][25][26] In order to gather more information on this hydrogen bond network we utilized IR spectroscopy to follow the hydration of HA by water vapor, starting from dry films several microns thick in order to prevent any saturation of bands, particularly, when these films were later hydrated. In order to carry out such a program, we repeated the procedure for the hydration of BSA.…”
Section: Introductionmentioning
confidence: 99%